Do you wanna dance? Tales of trust and driving trust factors in robot medication counseling in the pharmacy context - Hägglund, Susanne; Andtfolk, Malin; Rosenberg, Sara; Wingren, Mattias; Andersson, Sören; Nyholm, Linda (Frontiers in Robotics and AI, 2024)
Introduction: The sustainable implementation of socially assistive robots in a pharmacy setting requires that customers trust the robot. Our aim was to explore young adults’ anticipations of and motives for trusting robot medication counseling in a high-stakes scenario.Methods: Through a co-creation approach, we co-designed a prototype application for the Furhat platform together with young adults. In-lab testing of a pharmacy scenario, where the robot provides medication counseling related to emergency contraceptive pills, was conducted to deepen our understanding of some factors driving young adults’ initial trust establishment and anticipations of interacting with a robot in a high-stakes scenario. Qualitative data from interviews with six study participants were analyzed using inductive, reflexive thematic analysis and are presented through a narrative approach.Results: We outline five tales of trust characterized by personas. A continuum of different anticipations for consulting a robot in medication counseling is presented, ranging from low to high expectations of use. Driving factors in the initial trust establishment process are position, autonomy, boundaries, shame, gaze, and alignment.Discussion: The article adds to the understanding of the dimensions of the multifaceted trust concept, of driving trust factors, and of the subsequent anticipation to trust robots in a high-stakes pharmacy context.